2018
DOI: 10.32668/jitek.v6i1.79
|View full text |Cite
|
Sign up to set email alerts
|

Biskuit “Fishbean” sebagai Alternatif MP-ASI Lokal Tinggi Protein dan Vitamin A

Abstract: Less energy protein (PEM) and vitamin A deficiency have a close relationship. PEM in children can lead to a deficiency of vitamin A because it can lead to inhibition of absorption, transport, and the conversion of vitamin A. One of the local food sources of protein that can be used as a complementary feeding biscuits are catfish and red beans (Pangasius spp). This study aims to analyze the contribution of complementary feeding baby biscuit with substitution catfish and red beans on the adequacy of protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…(Sekhon, 2014). Intake of protein and vitamin A is increased by being given local supplementary food (Yuliantini et al, 2018) Rathnayake, et al (2012 with their study in Sri Lanka showed the diversity of food consumption as an indicator that can represent the nutritional adequacy of the community. Capanzana, et al (2018) stated the prevalence in the Philippines coastal households of wasting in children aged 0-60 months was 7.9%.…”
Section: Introductionmentioning
confidence: 99%
“…(Sekhon, 2014). Intake of protein and vitamin A is increased by being given local supplementary food (Yuliantini et al, 2018) Rathnayake, et al (2012 with their study in Sri Lanka showed the diversity of food consumption as an indicator that can represent the nutritional adequacy of the community. Capanzana, et al (2018) stated the prevalence in the Philippines coastal households of wasting in children aged 0-60 months was 7.9%.…”
Section: Introductionmentioning
confidence: 99%